Physical Education, its purpose in Higher Education. Teacher's opinions/La Educación Física, su finalidad en la Educación Superior. Opiniones del profesor - Rasciel de la Caridad Zayas Acosta; Faustino Camejo León; Manuel Rafael Valdés Portilla; Alexis Rodríguez Madera (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The third improvement of Higher Education in Cuba, started in the academic year 2016-2017, brought about deep transformations, characterized by uncertainty and the dynamics of change and such situation demands to propitiate a general knowledge of the educational processes and actions. This work aimed to know the opinions of Physical Education teachers of the University "Hermanos Saíz Montes de Oca" of Pinar del Rio (UPR in Spanish) about the purpose of this discipline and the knowledge they have about its different models. From a qualitative approach, the knowledge of 18 teachers was explored, based on the dialectical-materialistic method. The interview was used as an instrument to collect information. The results allowed to know those variables that determine the purpose of Physical Education, from the model assumed, as well as to glimpse some of the limitations that hinder the integral education of the graduate. It is concluded with some proposals to advance towards a Physical Education that integrates the different models and trends and with future lines of research on the subject.